Sistem Informasi Manajemen Event Pekan Olahraga Seni Desa (PORSENIDES) Beraban Menggunakan Framework Larayer - ayu nila dewi (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2021)
The Village Arts Sports Week (PORSENIDES) is a routine activity held by the Youth Organization every year in Beraban Village. There are problems that occur in the implementation of this activity, namely the registration process and data management still using a manual system, thus hampering the registration process and data management in PORSENIDES. Because of this problem, a Beraban Art Village Sports Week Event Management Information System (PORSENIDES) was created using the Laravel Framework. Designed to help manage data and simplify registration via the website. In making the system using the waterfall method, using the PHP programming language with the Laravel Framework, and using the MySQL database. Testing on this system is carried out using the Black Box Testing method which runs as expected and in the form of distributing questionnaires to 30 respondents which measures the level of satisfaction and effectiveness of users of this system. From the results of the questionnaire recapitulation, the percentage of 90% is included in the